West Nile Virus Seroprevalence in a Selected Donkey Population of Namibia - Molini, Umberto; Franzo, Giovanni; Nel, Hannah; Khaiseb, Siegfried; Ntahonshikira, Charles; Chiwome, Bernard; Baines, Ian; Madzingira, Oscar; Monaco, Federica; Savini, Giovanni; D'Alterio, Nicola (Frontiers in Veterinary Science, 2021)
West Nile Virus (WNV) is a mosquito-borne virus enzootically maintained in birds. However, it can incidentally infect other species, leading to sometimes severe clinical consequences like in horses and especially human beings. Despite the topic relevance, the presence and distribution of WNV are currently unknown in Namibia. Several countries implement surveillance systems based on virus detection in birds, mosquitoes and vertebrate species including horses. The present study aimed to fill this knowledge gap by serologically evaluating WNV exposure in Namibian donkeys, whose population is remarkably bigger than the horse one. Forty-seven out of 260 sampled animals showed neutralizing antibodies against WNV (18.07% [95%CI=13.59-23.30%]), demonstrating its circulation in all country territory, although with apparent regional differences. On the contrary, no association with animal age or sex could be identified. The present study demonstrates the widespread presence of WNV in Namibia as well as the practical utility and effectiveness of donkeys as sentinels for infection surveillance. Due to clinical relevance, vaccination campaigns should be considered for horses of high economic or genetic value. Additionally, the burden of WNV infection on human health should be carefully evaluated